What is in a “common” name? A call for consistent terminology for nonnative Sus scrofa - David A. Keiter; John J. Mayer; James C. Beasley (Wildlife Society Bulletin)
ABSTRACT Sus scrofa is both a destructive invasive species and a popular game animal in many parts of the world, but there is a lack of consistency and accuracy in how scientists and wildlife managers refer to wild‐living members of the species. The growing importance of this invasive species necessitates that scientists, managers, and policy‐makers standardize use of a common name in a taxonomically accurate manner to effectively communicate to the general public and scientific community. In this commentary, we discuss the current terminology used for S. scrofa and, based upon the history of introductions of this species, propose that these animals be referred to as wild pigs within their introduced range unless it is known that the population consists of genetically pure wild boar or domestic pigs that have recently been released and become feral. Use of the term “wild pig” should reduce the potential to misclassify populations as a result of genetic introgression and evolution following release. Furthermore, we recommend that, when appropriate, the terms “nonnative” or “invasive” be included to describe wild pigs in their introduced range to emphasize their negative impacts on natural and anthropogenic environments. The effective control of wild pig populations considered to be invasive will require informed public support and sound scientific management, necessitating clear communication about this species among the research community, wildlife managers, and the general public. © 2016 The Wildlife Society.